2010
DOI: 10.1264/jsme2.me09165
|View full text |Cite
|
Sign up to set email alerts
|

A New Fungal Endophyte, Helminthosporium velutinum, Promoting Growth of a Bioalcohol Plant, Sweet Sorghum

Abstract: A new fungal isolate that grows endophytically in sweet sorghum was identified as Helminthosporium velutinum Link ex Ficinus & Schubert. Light-microscopy of cross-sections of colonized sweet sorghum roots showed that the intercellular, pigmented hyphae of the fungus was mostly limited to the epidermal layer and formed outer mantle-like structures. This endophyte has the ability to significantly increase sweet sorghum biomass. This is the first report of Helminthosporium as an endophyte and could help realize s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…DSE fungi consist of a diverse group, are distributed worldwide, and are associated with a broad range of hosts that include around 600 species of plants from 320 genera and 114 families, such as Poaceae and Solanaceae, especially under harsh climatic conditions (1, 17, 33). To date, however, only 9 DSE species, Chloridium paucisporum , Leptodontidium orchidichola , Phialocephala dimorphosphora , P. fortinii , Phialophora finlandica , Meliniomyces variabilis , Heteroconium chaetospira , Veronaeopsis simplex , and Helminthosporium velutinum , have been reported (6, 17, 22, 23). Most of these DSE species were isolated from northern coniferous and boreal forests in nutrient-poor soils, except Heteroconium chaetospira , Veronaeopsis simplex , and Helminthosporium velutinum , three species of different genera, all isolated from coniferous rainforests, including freshwater in Japan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DSE fungi consist of a diverse group, are distributed worldwide, and are associated with a broad range of hosts that include around 600 species of plants from 320 genera and 114 families, such as Poaceae and Solanaceae, especially under harsh climatic conditions (1, 17, 33). To date, however, only 9 DSE species, Chloridium paucisporum , Leptodontidium orchidichola , Phialocephala dimorphosphora , P. fortinii , Phialophora finlandica , Meliniomyces variabilis , Heteroconium chaetospira , Veronaeopsis simplex , and Helminthosporium velutinum , have been reported (6, 17, 22, 23). Most of these DSE species were isolated from northern coniferous and boreal forests in nutrient-poor soils, except Heteroconium chaetospira , Veronaeopsis simplex , and Helminthosporium velutinum , three species of different genera, all isolated from coniferous rainforests, including freshwater in Japan.…”
mentioning
confidence: 99%
“…Most of these DSE species were isolated from northern coniferous and boreal forests in nutrient-poor soils, except Heteroconium chaetospira , Veronaeopsis simplex , and Helminthosporium velutinum , three species of different genera, all isolated from coniferous rainforests, including freshwater in Japan. Furthermore, recent studies showed multiple useful traits, such as nitrogen provision, growth promotion, and disease suppression, in host plants to be associated with these three taxa (6, 18, 19, 35). Based on these findings, DSE populations in Japan may be more diverse than previously thought and include other undescribed species.…”
mentioning
confidence: 99%
“…Therefore, to our knowledge, this study is the first report involving DSEs in such environments. Three of the isolates used in the present study, i.e., H. velutinum isolate 41-1, V. simplex isolate Y34 and P. ibarakiensis isolate I.4-2-1, have already been reported to support plant growth under nutrient-deficient and other acidic pH conditions but not in contaminated conditions [30] , [31] , [32] . These results shed a light on a new field of use of these isolates.…”
Section: Discussionmentioning
confidence: 83%
“…DSEs are defined as conidial or sterile ascomycetous fungi that colonize the root tissues of diverse plants intracellularly and intercellularly without any harmful effects or typical mycorrhizal structure formation ( 2 , 23 , 29 ). Previous findings indicated that DSEs have beneficial features for host plants, such as promoting plant growth, enhancing host tolerance against environmental stresses, and deterring encroachment by phytopathogens ( 10 12 , 44 ). Since DSEs may be easily isolated from the environment and artificially cultured as a granular inoculum for plants ( 23 , 28 , 50 ), they are expected to become useful biofertilizers and bioagents for preventing soil disease.…”
mentioning
confidence: 99%